Nature-Inspired Framework for Hyperspectral Band Selection - Nakamura, Rodrigo Y. M. [UNESP]; Garcia Fonseca, Leila Maria; Santos, Jefersson Alex dos; Torres, Ricardo da S.; Yang, Xin-She; Papa, João Paulo [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2014)
Although hyperspectral images acquired by on-board satellites provide information from a wide range of wavelengths in the spectrum, the obtained information is usually highly correlated. This paper proposes a novel framework to reduce the computation cost for large amounts of data based on the efficiency of the optimum-path forest (OPF) classifier and the power of metaheuristic algorithms to solve combinatorial optimizations. Simulations on two public data sets have shown that the proposed framework can indeed improve the effectiveness of the OPF and considerably reduce data storage costs.
Keywords: Evolutionary computation; heuristic algorithms; hyperspectral imaging; image classification; pattern recognition